Profiling Senyawa Metabolit Sekunder Fraksi Aktif Antihiperkolesterolemia Dari Herba Ketumpang Air (Peperomia pellucida L) - Rudiana, Tarso; Indriatmoko, Dimas Danang; Rohimah, Neneng; Afandi, Farhan Riza (Jurnal Farmasi Udayana, 2022)
Herba ketumpang air ( Peperomia pellucida L) contains bioactive compounds such as alkaloids, saponins, flavonoids, and steroids which are thought to be efficacious as antihypercholesterolemia. The purpose of this study was to determine the effectiveness of herba P. pellucida extracts as antihypercholesterolemia in vitro and characterize the active fraction. Extraction using ultrasonication methods with stratified organic solvents, such us n-hexane, ethyl acetate, and methanol. The fraction of n-hexane, ethyl acetate, and methanol were tested for cholesterol reduction activity in vitro by photometry method, cholesterol was reacted with Lieberman-Burchard reagents then analyzed using a UV-Vis spectrophotometer. The fraction that has the best activity is characterized by using a Liquid Chromatographic Mass Spectrometer (LCMS). Ethyl acetate fraction had the best activity to reduce cholesterol with a value EC 50 of 196.43 ppm. Based on phytochemical tests the active fraction of ethyl acetate contains alkaloids, flavonoids, saponins, and steroids. Results of LCMS analysis of ethyl acetate fraction at a retention time of 4.97; 7.82; and 10.80 are thought to contain active compounds of the flavonoid group namely velutin, casticin, and dihydrochalcone.